The Factors Influencing Prenatal Development - Beresnevičienė, Danguolė (Acta Paedagogica Vilnensia, 1999)
[full article and abstract in Lithuanian; abstract in English] The article deals with the problem of the influences on prenatal development. After the analysis of the scientific literature, the author concludes, that the largest effects on the prenatal development are doing the following biological and psychophysical factors: maternal age, maternal nutrition, state of health and teratogens acting through males as well as through the females: tobacco, alcohol and drug using. In spite of the biological and psychophysical agents, psychological factors are able to improve or to hamper the psychophysical prenatal development. So the author is suggesting the parents to improve prenatal development through their positive attitude to the pregnancy: to stop to use alcohol, tobacco before the conception, to improve maternal nutrition, to avoid anxiety and to create positive, safe emotional climate in the family.